Brief O2 uploading during continuous hypothermic machine perfusion is simple yet effective oxygenation method to improve initial kidney function in a porcine autotransplant model. Issue 8 (21st February 2020) - Darius, Tom; Vergauwen, Martial; Smith, Thomas; Gerin, Isabelle; Joris, Virginie; Mueller, Matteo; Aydin, Selda; Muller, Xavier; Schlegel, Andrea; Nath, Jay; Ludwig, Christian; Dessy, Chantal; et al.
Abstract : With oxygenation proposed as a resuscitative measure during hypothermic models of preservation, the aim of this study was to evaluate the optimal start time of oxygenation during continuous hypothermic machine perfusion (HMP). In this porcine ischemia‐reperfusion autotransplant model, the left kidney of a ±40 kg pig was exposed to 30 minutes of warm ischemia prior to 22 hours of HMP and autotransplantation. Kidneys were randomized to receive 2 hours of oxygenation during HMP either at the start (n = 6), or end of the perfusion (n = 5) and outcomes were compared to standard, nonoxygenated HMP (n = 6) and continuous oxygenated HMP (n = 8). The brief initial and continuous oxygenated HMP groups were associated with superior graft recovery compared to either standard, nonoxygenated HMP or kidneys oxygenated at the end of HMP. This correlated with significant metabolic differences in perfusate (eg, lactate, succinate, flavin mononucleotide) and tissues (eg, succinate, adenosine triphosphate, hypoxia‐inducible factor‐1α, nuclear factor erythroid 2‐related factor 2) suggesting superior mitochondrial preservation with initial oxygenation. Brief initial O2 uploading during HMP at procurement site might be an easy and effective preservation strategy to maintain aerobic metabolism, protect mitochondria, and achieve an improved early renal graft function compared with standard HMP or oxygen supply shortly at the end of HMP preservation. Abstract : Brief initial oxygen uploading during hypothermic machine perfusion might be an easy and effective preservation strategy to maintain aerobic metabolism, protect mitochondria, and achieve improved early renal graft function compared with standard cold perfusion without additional oxygen supply.